Pulsation energy of the Couette–Taylor flow in gaps of multicylinder counter-rotating rotors - A.F. Serov; V.N. Mamonov; A.D. Nazarov (Учёные записки Казанского университета: Серия Физико-математические науки, 2017)
The results of the experiments on thermal energy separation during the rotation of two coaxial counter-rotating multislot “rotors” that form a system of cylindrical ring channels filled with viscous working fluid have been presented. The Couette–Taylor flow occurs in such a system of annular channels. The proposed design has been viewed as a model of the heat generator with the driving device having two counter-rotating (rotating towards each other) wind engines. During the operation, the working fluid heated in the annular channels due to the high shear stresses in the circulating loop containing a heat exchanger to transfer heat to the battery heat. The kinetic energy of the driving device is completely converted into the heat energy. During the experiment, we have performed the direct measurement of the moment of forces of resistance to rotation of the “rotor”, the energy spectra of pulsations at that moment, the heat power released during the operation of the device. The experiments have been carried out at four values of the viscosity of the working fluid in the range of variation of the angular speed of rotation of the “rotor” Ω = (6–30) rad/s. The influence of the geometrical parameters of the heat source on the efficiency of converting the kinetic energy of a mechanical actuator into thermal energy has been considered. The obtained results have been analyzed. It has been shown that the proposed design of the heat generator allows to create a device with the given power to operate in the range of small angular velocities of rotation of the “rotor”.